A systematic review of systematic review methodology in plastic surgery journals. Issue 9 (September 2022) - Savage, Nicholas; Savage, Simon; Doherty, Zakary; Rozen, Warren M.; Hunter-Smith, David J.; Goldie, Stephen J.
Abstract: Introduction: Systematic reviews (SR) and meta-analyses (MA) are described as the top level of evidence in clinical research and are commonplace in plastic surgery literature. Their quality is limited both by the reliability of primary studies and the method of aggregating data. This study analysed the overall quality of SR's in plastic surgery and identified influencing factors. Materials and methods: The paper critically appraised SR's published in three prominent plastic surgery journals between July 2019 and July 2020. Study selection and appraisal was performed in duplicate. Articles were assessed using A Measurement Tool to Assess Systematic Reviews (AMSTAR). Results: Seventy-six studies were included. 52 (68%) were SR's only and 24 (32%) included meta-analysis (MA) as well. The most common subspecialty areas included breast, craniofacial and hand. 78% of studies followed the PRISMA guidelines. The median (min, max) AMSTAR score was 3.5 (0–7). SR's with MA had significantly higher AMSTAR scores ( p <0.001) than SR's alone, with median scores of 5 and 3 respectively. Papers from China had significantly higher AMSTAR scores than the USA. Craniofacial SR's had significantly higher scores than all other subspecialty areas. Most SR's reviewed concluded that there is currently inadequate primary research to make a conclusion and recommended more research be carried out in that area. Conclusions: This systematicreview found overall that the quality of research methodology in Plastic Surgery SRs is low, and their conclusions of limited value. Surgeons should be familiar with SR and MA methodology, so they can exercise better judgement in applying findings to clinical practice.